The Effects of Individual-Level and Group-Level Trust on Willingness to Communicate in the Group Language Learning - Ito, Takehiko; Furuyabu, Mariko; Toews-Shimizu, Jennifer (Frontiers in Education, 2022)
This study examined the effects of individual-level and group-level trust on willingness to communicate (WTC) in a second language, targeting Japanese university students in a group-language (English) learning setting. Although the effects of group language learning on students’ learning attitudes have been examined extensively, no study has examined group-level factors in a group-language learning setting. A questionnaire survey was conducted thrice per semester. Multilevel analysis found that individual-level trust in group members positively influenced individual-level WTC in English, and group-level trust in group members also positively influenced group-level WTC in English repeatedly through one semester. Moreover, the degree of group-level WTC in English changed after the mid-semester. This study contributes to the literature on group-language learning, and has implications for language education where educators must be mindful not only of each student’s characteristics but also of each group’s characteristics to enhance their performance.